The city makers of Nairobi an African urban history - Ese, Anders 1979-; Ese, Kristin (Routledge research in urban planning and design, 2020)
"The City Makers of Nairobi re-examines the history of the urban development of Nairobi in the colonial period. Although Nairobi was a colonial construct with lasting negative repercussions, the African population's impact on its history and development is often overlooked. This book shows how Africans took an active part in making use of the city and creating it, and how they were far from being subjects in the development of a European colonial city. This re-interpretation of Nairobi's history suggests that the post-colonial city is the result of more than unjust and segregative colonial planning. Merging historical documentation with extensive contemporary urban theory, this book provides in-depth knowledge of the key historical roles played by locals in the development of their city. It argues that the idea of agency, a popular inroad to urban development today, is not a current phenomenon but one that has always existed with its many social, spatial and physical ramifications. An ideal read for upper-level undergraduate and graduate students studying history of urban development and theories, providing an in-depth case study for reference. The City Makers of Nairobi broaches interdisciplinary themes important to urban planners, social scientists, historians and those working with popular settlements in cities across the world"--